Efficacy of serratiopeptidase in third molar surgery. A systematic review and meta-analysis - Heber Arbildo-Vega; Alfredo Rendón-Alvarado; Tania Castillo-Cornock; Fredy Cruzado-Oliva; Alex Vidal-Mosquera; Hernán Vásquez-Rodrigo (Universidad de Concepción., 2023)
Objective: To determine the efficacy of serratiopeptidase in third molar surgery. Materials and Methods: A bibliographic search was carried out until April 2022, in the biomedical databases: Pubmed/Medline, Cochrane Central Registry of Clinical Trials, Scopus, Scielo and Google Scholar. Studies reporting the ef-ficacy of serratiopeptidase in third molar surgery, which were randomized clinical trials, in English and without time limits, were included. The RoB 2.0 tool was used to assess the risk of the included studies and the GRADEPro GDT tool to assess Results: The preliminary search yielded a total of 116 articles, discarding those that did not meet the selection criteria, leaving only 10 articles. Six articles entered a meta-analysis and found that serratiopeptidase reduces trismus but not reduce inflammation and pain after third molar surgery. Conclusions: The literature reviewed suggests that ser-ratiopeptidase is effective in reducing trismus after third molar surgery.